Validation of housekeeping genes for the normalization of RT-qPCR expression studies in oral squamous cell carcinoma cell line treated by 5 kinds of chemotherapy drugs - Song, W.; Zhang, W. H.; Zhang, H.; Li, Y.; Zhang, Y.; Yin, W.; Yang, Q. (Cellular and Molecular Biology, 2016)
Reverse transcription quantitative polymerase chain reaction (RT-qPCR) has become a frequently used strategy in gene expression studies. The relative quantification method is an important and commonly used method for the evaluation of RT-qPCR data. The key of this method is to identify an applicable internal control gene because the usage of different internal control genes may lead to distinct conclusions. Herein, we report the validation of 12 common housekeeping genes for RT-qPCR for gene expression analysis in the Oral squamous cell carcinoma (OSCC) cell line (KB and Tca-8113) treated by 5 kinds of Chemotherapy Drugs. The gene expression stability and applicability of the 12 housekeeping gene candidates were determined using the geNorm, NormFinder, and BestKeeper software programs. Comprehensive analyzing the results of the three software, ALAS1/GAPDH, ALAS1 and GUSB were suggested to be the most stable candidate genes for the study of both KB and Tca-8113 cell line together, KB cell line, and Tca-8113 cell line, respectively. This study provides useful information to normalize gene expression accurately for the investigation of target gene profiling in cell lines of OSCC. Further clarification of tumor molecular expression markers with our recommended housekeeping genes may improve the accuracy of diagnosis and estimation of prognostic factors as well as provide novel personalized treatments for OSCC patients.